Pemanfaatan Teknologi Artificial Intelligence (AI) Mesin Pencari Informasi Pada Pesantren Bahrul Uluum Al-Kamal Asahan - Suparmadi, Suparmadi; Zulkarnain, Zulkarnain; Akmal, Akmal (STMIK Royal, 2024)
The use of Artificial Intelligence Technology aims to develop knowledge through information search engines so that it can help students, teachers and schools. The targets that will become benchmarks in community service include various counseling, presentations and questions and answers. With technology involving artificial intelligence in it, it makes it easier for pupils and students to search for information obtained from various sources. This data collection technique is interviews with previously prepared data, both observation and documentation and using relevant library methods. The aim of this service at the Bahrul Uluum Al Kamal Asahan Islamic boarding school is in the field of religious knowledge and can also understand Artificial Intelligence. By providing community service, it can help and increase knowledge outside of religious knowledge, namely artificial intelligence. Apart from that, it is also able to invite the community to be directly involved in its development. Keywords: IT; artificial intelligence; information systems